2007
DOI: 10.4049/jimmunol.179.12.8463
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Chemokine Receptor CXCR3 Inhibits T Cell Recruitment to Inflamed Joints and Decreases the Severity of Adjuvant Arthritis

Abstract: T lymphocytes expressing the chemokine receptors, CCR2, CCR5, CXCR3, and CXCR6 are increased in inflamed tissues in rheumatoid arthritis. The role of CXCR3 in autoimmune arthritis induced in Lewis rats was investigated. CXCR3+ T cells migrated 2- to 3-fold more than CXCR3− T cells to inflamed joints in arthritic animals. CXCR3-expressing in vivo Ag-activated T lymphoblasts and in vitro-activated lymph node cells from arthritic animals were strongly recruited to the arthritic joints, and treatment with anti-CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 45 publications
4
68
0
Order By: Relevance
“…[51,60,[63][64][65] An antibody directed against CXCR3 not only reduced T cell recruitment to inflamed arthritic joints in a rat model of arthritis, but also prevented weight loss by the animals and decreased the severity of arthritis in general. [66] Indeed, the CXCL10 antibody MDX1100 (vide supra) will also be investigated in a Phase II trial for rheumatoid arthritis. [62] Last, a CXCL10 antibody suppressed metastasis of melanoma cells to the lymph nodes in mice.…”
Section: Cxcr3-ko (Cxcr3mentioning
confidence: 99%
“…[51,60,[63][64][65] An antibody directed against CXCR3 not only reduced T cell recruitment to inflamed arthritic joints in a rat model of arthritis, but also prevented weight loss by the animals and decreased the severity of arthritis in general. [66] Indeed, the CXCL10 antibody MDX1100 (vide supra) will also be investigated in a Phase II trial for rheumatoid arthritis. [62] Last, a CXCL10 antibody suppressed metastasis of melanoma cells to the lymph nodes in mice.…”
Section: Cxcr3-ko (Cxcr3mentioning
confidence: 99%
“…Thus, blockade of the CXCR4 receptor for SDF-1/CXCL12 with the synthetic non-peptide antagonist, AMD3100, inhibited murine CIA in IFN-receptordeficient mice in both a prophylactic as well as a therapeutic protocol [139]. Recently, Mohan et al [140] examined the role of CXCR3 in murine adjuvant arthritis (AA) and found that CXCR3 + T-cells migrated 2-to 3-fold faster than CXCR3-T-cells into inflamed joints, suggesting the importance of this chemokine receptor for T-cell recruitment. The blockade of CXCR3 with a monoclonal antibody resulted in inhibition of T-cell recruitment by 40-60%, a delay in the onset of arthritis, and reduced severity of joint inflammation with a > 50% decrease in the clinical arthritis score [140].…”
Section: Chemokine and Chemokine Receptor Targeting Strategies In Ramentioning
confidence: 96%
“…Recently, Mohan et al [140] examined the role of CXCR3 in murine adjuvant arthritis (AA) and found that CXCR3 + T-cells migrated 2-to 3-fold faster than CXCR3-T-cells into inflamed joints, suggesting the importance of this chemokine receptor for T-cell recruitment. The blockade of CXCR3 with a monoclonal antibody resulted in inhibition of T-cell recruitment by 40-60%, a delay in the onset of arthritis, and reduced severity of joint inflammation with a > 50% decrease in the clinical arthritis score [140]. CXCR3 blockade also resulted in a 50-60% decrease in neutrophil accumulation in the synovium as well as reducing weight loss in the arthritic animals.…”
Section: Chemokine and Chemokine Receptor Targeting Strategies In Ramentioning
confidence: 98%
“…Some of the newly developed anti-chemokine [44] and anti-adhesion molecule [45] antibodies have also clearly demonstrated efficacy and disease-modifying activity in animal models of RA. However, an anti-chemokine monoclonal antibody therapy met with less success in a recently completed human RA clinical trial [46].…”
Section: The Existing Ra Therapuetic Armamen-tarium Is Substantialmentioning
confidence: 97%